2021
DOI: 10.2478/atd-2021-0012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Online Learning on Transfer Student Success

Abstract: Introduction: Online learning increased rapidly during the 2020 school year due to COVID-19. While online learning was perhaps the only realistic response to the health crisis, students differ in terms of their success with online learning. One particular group which may be vulnerable to problems with online learning is transfer students. Transfer students may be coming from smaller, in-person classes and are now put into fully online environments. This paper studies the performance of transfer students in onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…For example, Mead et al (2020) found that even though low-income students tend to receive lower course grades than non-low-income students in both online and in-person biology courses, the grade disparity was larger in courses using an online format. Likewise, Metzgar (2021) found that transfer students in an online economics course had lower final course grades than transfer students who completed the same course in-person.…”
Section: Students' Perceptions Of Benefits and Costs Of Online Learningmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, Mead et al (2020) found that even though low-income students tend to receive lower course grades than non-low-income students in both online and in-person biology courses, the grade disparity was larger in courses using an online format. Likewise, Metzgar (2021) found that transfer students in an online economics course had lower final course grades than transfer students who completed the same course in-person.…”
Section: Students' Perceptions Of Benefits and Costs Of Online Learningmentioning
confidence: 97%
“…Even though previous research primarily concentrated on the benefits and costs of online education for students in general, there is a growing body of work that explores these benefits and costs of online education specifically for students, such as those from low-income backgrounds (Mead et al, 2020), transfer students (Metzgar, 2021), and within specific domains like engineering (Manea et al, 2021). For example, Manea et al (2021) showed that engineering students, like other students, appreciated the ability to review recorded lectures at any time and the possibility to participate in class from anywhere.…”
Section: Students' Perceptions Of Benefits and Costs Of Online Learningmentioning
confidence: 99%
“…The effectiveness of online learning for undergraduate students in 13 schools across seven countries and regions in Asia was assessed through a questionnaire-based online survey. Metzgar [15] pointed out that, while online learning may be the only realistic response to the health crisis, students have varying degrees of success with online learning. One specific group that may be susceptible to challenges with online learning is transfer students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This transition is reported to be imposing a variety of constraints caused by, for example, lack of technical equipment to launch online teaching (Altavilla, 2020;Mahyoob, 2020;Spurrier et al, 2020), limited access to schools as mobility is restricted (Metzgar, 2021), insufficient digital literacy skills possessed by teachers and learners (Atmojo & Nugroho, 2020), no or inappropriate guidance on how to put ERT into practice (Toquero, 2020), unclear assessment regulations (Balbay & Erkan, 2012), or teaching and learning experiences that are perceived demotivating, ineffective and exacerbating social inequities (Shin & Hickey, 2021) and affecting mental health (Karakose et al, 2022;Sahu, 2020).…”
Section: Emergency Remote Teachingmentioning
confidence: 99%